Ischaemic heart disease assessment by cardiovascular magnetic resonance imaging. Issue 1019 (13th September 2010) - Raj, Vimal; Agrawal, S K
Abstract : Ischaemic heart disease (IHD) related mortality has been on the decline, although its prevalence has been on the rise since the late 1970s. One of the contributing factors to this decline has been improved diagnosis and therapeutic management. Every clinician seeks to answer four key questions while evaluating patients with suspected or known IHD: What is the global ventricular function? What is the regional ventricular function? Is the myocardium viable? What is the status of the coronary arteries? In the past decade cardiovascular magnetic resonance (CMR) imaging has emerged as an important clinical technique with the potential of answering all the pertinent questions in a single study. This has led to a significant increase in demand and utilisation of this modality. However, many clinicians are not well versed with this technology, its clinical utility, limitations and future prospects. With the increasing prevalence of IHD, CMR imaging is likely to be used more often in its diagnosis, prognostication and management. The review describes the basic principles and practical aspects of CMR imaging, and then discusses in detail the role of CMR in the diagnosis and management of IHD, its complications, and its utility in patients with acute myocardial infarction.